Model Faktor Risiko Stunting Balita: Studi di Puskesmas Astambul, Kabupaten Banjar - Farhat, Yasir (Politeknik Kementerian Kesehatan Banjarmasin, 2026)
Stunting is a growth disorder caused by long-term chronic malnutrition. Based on e-PPGBM data, the prevalence of stunting among children under five at the Astambul Health Center was 20.89% in October 2023 and increased to 27.01% in February 2024. This study aimed to analyze the factors influencing stunting and to develop a model of its incidence among toddlers in the working area of Astambul Health Center, Banjar Regency. This research used an analytical observational design with a cross-sectional approach. A total of 96 mothers of under-five children were selected through purposive sampling. Data were collected through anthropometric measurements and structured interviews using questionnaires, then analyzed with multiple logistic regression. The results showed that most mothers had an ideal pregnancy interval (82.3%) and attended ≥4 antenatal visits. Most children had no history of infection, and maternal knowledge was generally good (86.5%). Complementary feeding was age-appropriate in 72.9% of cases. However, energy intake was insufficient in 61% of children, while protein intake was adequate in 64.6%. Basic immunization coverage was complete in 64.6% and exclusive breastfeeding was reported in 68.8%. The study found a significant effect of complementary feeding patterns on stunting. Children receiving inappropriate complementary foods for their age had 1.3 times higher risk of stunting. In conclusion, improving mothers’ knowledge through nutrition counseling and encouraging their active participation in health education programs are crucial strategies to prevent stunting.